2018
DOI: 10.1101/275339
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Electromechanics and Volume Dynamics in Non-excitable Tissue Cells

Abstract: Cell volume regulation is fundamentally important in phenomena such as cell growth, proliferation, tissue homeostasis and embryogenesis. How the cell size is set, maintained, and changed over a cell's lifetime is not well understood. In this work we focus on how the volume of non-excitable tissue cells is coupled to the cell membrane electrical potential and the concentration of membrane-permeable ions in the cell environment. Specifically, we demonstrate that a sudden cell depolarization using the whole cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…In this issue of Biophysical Journal, Yellin et al (9) present a promising method that could address these outstanding problems. Specifically, by using the whole-cell patch-clamp setup, Yellin and co-workers were able to precisely control the membrane potential of a single cell as well as monitor its volume change in an accurate and continuous manner.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In this issue of Biophysical Journal, Yellin et al (9) present a promising method that could address these outstanding problems. Specifically, by using the whole-cell patch-clamp setup, Yellin and co-workers were able to precisely control the membrane potential of a single cell as well as monitor its volume change in an accurate and continuous manner.…”
mentioning
confidence: 99%
“…Interestingly, Yellin et al ( 9) also found that, even when the surrounding osmolarity was kept at the same level, altering the concentration percentage of chloride or potassium ions in the culture fluid led to distinct volumetric response of cells, highlighting the importance of cross-membrane transport of individual ion species in the volume regulation of cells. Fortunately, on the basis of the platform developed in (9), it becomes possible to quantitatively measure, after proper fluorescent labeling (8,10), how the concentrations of different intracellular ions evolve under precisely controlled experimental conditions (e.g., at fixed level of membrane potential and/or extracellular concentration of individual ions), which will greatly help us understand the mechanism(s) behind such transmembrane ion exchange. Finally, by taking into account both the passive and active (by different ion channels/pumps) cross-membrane transport of major ions as well as water molecules, Yellin et al (9) propose a mathematical model to quantitatively explain the observed volumetric response of cells under different electromechanical cues in their experiment.…”
mentioning
confidence: 99%
See 1 more Smart Citation